The scalar-tensor theory of gravitation - Fujii, Yasunori (Cambridge monographs on mathematical physics., 2003)
A pedagogical overview of the theoretical ideas behind the cosmological constant problem, in particular the scalar-tensor theory, which is one of the most popular alternative theories of gravitation. Covering recent developments in the field, including branes and quintessence, it will be an invaluable resource for graduate students and researchers alike.